Sejarah Perkembangan Tarekat Qadiriyah wa Naqsyabandiyah di Pesantren Assalafi Al-Fithrah Surabaya 1985-2018 - Tsaniya Fani Ikrimah (Qurthuba: The Journal of History and Islamic Civilization, 2019)
Abstract: This study used a historical approach. According to Ibn Khaldun history in essence contains thoughts, research, and causes in detail about the realization of society and its foundations, as well as in-depth knowledge of the nature of various events. The establishment of the Assalafi Al-Fithrah Islamic boarding school and the Qadiriyah wa Naqshbandiyah sufi order which greatly influenced the community and as the formation of character figures during his life. The theory used is the theory of Louis Gosttschalk's influence and the cycle theory of Ibn Khaldun, as well as scrutinizing the influence of KH. Asrori Ishaqy in developing the sufi order (tarekat) and its up and downs in the development of leadership successionsThe study concluder that (1). KH. Asrori Ishaqy was born on August 17, 1950 in the Dar al-Ubudiyah Islamic boarding school Raudat al-Muta’allim Jati Purwo, Surabaya, which has been promoted to be the successor of the tarekat in Kedinding Lor. (2). The Qadiriyah Wa Naqshayahniyah tarekat is established by KH. Asrori Ishaqy in 1985 to Kedinding Lor. (3). The stratesy implemented by KH. Asrori Ishaqy in rutspreading the tarekat is lay inviting the “stranded” people of association of “orong-orong” to rhe Al-Khidmah. Keywords: Islamic Boarding School, tarekat